Herschel -ATLAS: Dust temperature and redshift distribution of SPIRE and PACS detected sources using submillimetre colours - Amblard, A; Cooray, A; Serra, P; Temi, P; Barton, E; Negrello, M; Auld, R; Baes, M; Baldry, I; Bamford, S; Blain, A; Bock, J; et al. (2010)
We present colour-colour diagrams of detected sources in the Herschel-ATLAS science demonstration field from 100 to 500 μm using both PACS and SPIRE. We fit isothermal modified black bodies to the spectral energy distribution (SED) to extract the dust temperature of sources with counterparts in Galaxy And Mass Assembly (GAMA) or SDSS surveys with either a spectroscopic or a photometric redshift. For a subsample of 330 sources detected in at least three FIR bands with a significance greater than 3σ, we find an average dust temperature of (28±8) K. For sources with no known redshift, we populate the colour-colour diagram with a large number of SEDs generated with a broad range of dust temperatures and emissivity parameters, and compare to colours of observed sources to establish the redshift distribution of this sample. For another subsample of 1686 sources with fluxes above 35 mJy at 350 μm and detected at 250 and 500 μm with a significance greater than 3σ, we find an average redshift of 2.2±0.6. © 2010 ESO.